Retrospective descriptive observational study of patients who presented to an Australian hospital emergency department with neck soft tissue injury. (20th March 2019) - Nikles, Jane; Khan, Subaat; Leou, John; Keijzers, Gerben; Ng, Joanna; Bond, Catherine; Nakamura, Gota; Le, Rhonda; Sterling, Michele
Abstract: Objective: To describe clinical presentation and management of neck soft tissue injury in an Australian ED. Methods: This is a retrospective cohort study conducted in a tertiary hospital ED in Queensland, Australia. This study included all patients aged 18–65 years presenting with neck sprain/strain in 2016. Main outcome measures are patient demographics, comorbidities, presentation, acute management and follow up. Results: Of 339 patients, 176 (52%) had cervical computed tomography (CT) scans and 3% plain radiographs. Two had fractures (CT yield of 2/176; 1.1%) and three were admitted with neurological symptoms, leaving 334 patients. Of 264 patients receiving medications in the ED, simple analgesia + oral opioid (146, 55.3%) was most frequently used, followed by simple analgesia (89, 33.7%) and opioid + benzodiazepine +/− simple analgesia (16, 6%). Opioids were prescribed for 169 (64%) (including i.v. opioids for 34 [12.9%] and for 85/97 (88%) with pain scores ≤4), and benzodiazepines for 22 (8.3%). Ten (3%) were referred for physiotherapy management in ED and eight (2.4%) for outpatient physiotherapy follow up. Of 113/334 (33.8%) receiving discharge prescription, 60 (53.1%) were prescribed oral opioid + simple analgesia, 37 (32.7%) oral opioids and seven (6.2%) opioids + benzodiazepines; 205 (61%) were discharged without a recorded follow‐up plan. Conclusions: There is large practice variation in management of neck soft tissue injury in ED. Over half of the patients received CT scans with modest yield. Opioids were commonly used both in ED and on discharge. There is need for a standard management plan to be developed for patients presenting with acute neck soft tissue injury.